A conceptual model of corporate social responsibility dimensions, brand image, and customer satisfaction in Malaysian hotel industry - Mohammed, Abdulalem; Rashid, Basri (Kasetsart Journal of Social Sciences, 2018)
Corporate social responsibility (CSR) has become a core concept in the context of the hotel industry where it is considered as a significant factor in competition and a firms’ survival, primarily because CSR influences customer satisfaction. However, there are still few studies examining the relationship between the dimensions of CSR (economic, philanthropic, legal, and ethical) and customer satisfaction, particularly in the Malaysian hotel sector. Additionally, some studies have contended that CSR activities may indirectly affect customer satisfaction, and some factors may potentially mediate the effects of CSR activities on satisfaction. Hence, the present study developed a conceptual model to explain the relationship between the dimensions of CSR, brand image and customer satisfaction. According to the proposed model, CSR dimensions may positively influence customer satisfaction, with brand image mediating the relationship.